Cured material based on the synergistic effect of micp-alkali activation and a method for producing the same

CN123003236APending Publication Date: 2026-10-30EAST CHINA JIAOTONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611187085.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]为了克服现有碱激发注浆材料韧性不足、易收缩开裂,以及传统MICP技术无法在强碱性环境中有效工作且矿化不均匀的缺陷,本发明提供一种基于MICP-碱激发协同作用的固化材料及其制备方法

Benefits of technology

[0051]本发明利用粉煤灰、高炉矿渣及钢渣等工业固体废弃物作为主要胶凝原料,通过碱激发反应形成具有胶结性能的凝胶结构,实现了工业废渣的高值化资源利用,降低了传统水泥材料的使用量,从而有效减少了能源消耗及二氧化碳排放,具有良好的绿色低碳环保效益。与此同时,引入微生物诱导碳酸钙沉淀(MICP)技术,通过微生物矿化作用在土颗粒表面及孔隙内部生成碳酸钙晶体,可进一步填充土体孔隙、增强颗粒间胶结作用,从而显著提高软土的密实性、抗压强度及抗渗性能。此外,本发明中碱激发胶凝体系与MICP矿化体系之间能够形成协同增强效应,经实验验证(详见对比例1和2),碱激发体系(不含MICP)28天强度为22MPa,MICP体系(不含碱激发)28天强度为6.5MPa,二者理论加和为28.5MPa;而实施例1中两者协同作用后的28天强度达到32MPa,显著高于二者单独作用强度之和,相对增幅达12.3%。该数据有力证明了本发明绝非各组分效果的简单叠加,而是产生了“1+1>2”的预料不到的协同增强效果。具体而言,碱激发凝胶体系与MICP碳酸钙沉积之间并非简单的物理混合或独立作用,而是存在显著的化学与物理协同效应—凝胶网络为碳酸钙提供了优先成核位点,而碳酸钙晶体又填充了凝胶骨架的微孔隙并桥接颗粒界面,形成了“凝胶-晶体”互锁的致密复合结构,该结构无法通过单一体系叠加实现。碱激发形成的凝胶网络可为碳酸钙晶体提供沉积载体,而生成的CaCO3晶体又能够作为凝胶产物的成核位点,进一步促进浆体结构致密化,有效降低材料收缩开裂风险并提高长期耐久性。本发明通过引入外加电场,解决了传统MICP工艺中Ca2+与CO32-迁移速率受限于自由扩散、矿化分布不均的核心技术难题。电场作用下的电迁移效应可定向加速钙离子向微生物富集区输送,同时通过电化学反应中和局部高碱环境,使碳酸钙生成量提升37.8%~72%(见实施例3-5),孔隙率降低22%~39%,实现了矿化反应的时空可控性与均匀性,显著提升了材料的早期强度与致密性。该固化材料兼具良好的流动性、可注性及快速固化性能,可广泛应用于隧道工程、地下工程及道路软土地基加固等领域,具有较高的工程应用价值和推广前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003236A_ABST
    Figure CN123003236A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of low-carbon resource utilization of industrial solid waste, and relates to a solidified material based on the synergistic effect of MICP-alkali activation, which is formed by mixing component A and component B, the component A is alkali-activated industrial waste residue slurry, and the component B is mineralized bacteria liquid composed of alkali-resistant bacillus, urea and calcium source which are gradient alkali-adapted and domesticated, and the application further discloses a preparation method of the solidified material, in which the industrial waste residue is mixed with an alkali activator to prepare pulp, and then mixed with the bacteria liquid to inject the pulp, and a direct current electric field is applied after the injection of the pulp. Through the synergistic enhancement of the alkali-activated cementation reaction and the microbial mineralization reaction, combined with the directional migration effect of the electric field, the mechanical strength and the impermeability of the solidified body are significantly improved, and the resource utilization of the industrial solid waste is realized, so that the application is suitable for soft soil reinforcement and grouting treatment in tunnels, underground and road engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of low-carbon resource utilization technology of industrial solid waste, specifically involving a solidification material based on the synergistic effect of MICP-alkali activation and its preparation method, which is suitable for grouting reinforcement and soft soil foundation solidification treatment in tunnel engineering, underground engineering and road engineering under high water pressure and strong corrosive environment. Technical Background

[0002] With the large-scale development and utilization of transportation infrastructure and urban underground space in my country, the construction of tunnel projects, underground utility tunnels, and deep foundation pits for high-rise buildings is gradually extending to areas with complex geological conditions. Soft soil, characterized by high water content, high compressibility, and low bearing capacity, is highly susceptible to engineering problems such as uneven settlement, instability, and slippage. Simultaneously, many existing tunnels and underground projects have entered the maintenance and renovation phase, leading to a surge in demand for projects such as grouting repair behind shield tunnel walls and sealing of water-rich fractured zones. In these engineering scenarios, grouting and curing materials are core elements for ensuring project safety and long-term service performance. An ideal grouting material must not only possess excellent fluidity, injectability, and controllable setting time, but also high mechanical strength, excellent impermeability and durability, and good environmental compatibility.

[0003] Traditional cement-based grouting materials (such as ordinary silicate cement grout, cement-water glass two-component grout, etc.) are widely used due to their mature technology and stable strength development. However, these materials have inherent defects: on the one hand, the cement production process is accompanied by high energy consumption and large amounts of carbon dioxide emissions, which does not conform to the national policy of green and low-carbon sustainable development; on the other hand, traditional cement grout is prone to micro-cracks due to drying shrinkage during the hardening process, and its long-term durability is insufficient in underground high water pressure and corrosive ion environments, which can easily lead to the failure of the grouting structure.

[0004] To overcome the aforementioned shortcomings, the preparation of low-carbon cementitious materials from industrial solid waste has become a research hotspot. Fly ash, blast furnace slag, and steel slag are typical siliceous aluminous industrial solid wastes, produced in huge quantities with low comprehensive utilization rates. By activating the active components in these waste residues with alkali activators, products such as hydrated calcium silicate (CSH) and hydrated aluminosilicate (NASH) with cementing properties can be generated, resulting in higher mechanical strength. Alkali-activated solid waste materials have advantages such as low carbon emissions, economical cost, and strong resistance to chemical corrosion, showing great potential to replace traditional cement-based materials. However, existing alkali-activated grouting materials often suffer from large shrinkage, easy cracking, and high brittleness during the hardening process, which limits their application under dynamic loads and complex geological conditions.

[0005] Microbially induced calcium carbonate precipitation (MICP), an emerging biomineralization technology, utilizes urease-producing microorganisms, such as *Sporosarcina pasteurii*, to hydrolyze urea, generating carbonate ions that combine with calcium ions to form cementing calcium carbonate crystals. This technology has been proven to effectively fill soil pores and cement loose particles, thereby improving soil strength and impermeability.

[0006] However, the mineralization efficiency of traditional MIP technology is limited by the ion diffusion rate, making it difficult to meet the requirements of large-scale engineering projects in terms of reinforcement depth and uniformity. The application of existing MIP technology in alkaline-activated systems still has certain limitations. First, alkaline-activated slurries are usually highly alkaline (pH>12), making it difficult for conventional microorganisms to survive in this environment; their urease activity is rapidly lost, resulting in extremely low biomineralization efficiency. Second, in traditional MIP processes, Ca... 2+ With CO3 2- The migration rate is limited by free diffusion, resulting in a slow mineralization reaction rate and uneven distribution of the generated calcium carbonate. This makes it difficult to form an effective interlock with the cementitious framework of the alkali-activated reaction, thus affecting the overall reinforcement effect. Thirdly, existing technologies mostly focus on the development of single alkali-activated materials or microbial reinforcement under electric field assistance, and have not yet formed a systematic composite grouting material system and its synergistic preparation method that deeply integrates MICP, alkali-activated cementation, and electric field regulation. More importantly, there is a common technical bias in this field that "the high-alkaline environment of the alkali-activated system is lethal to microorganisms," which has led to the long-term neglect of research paths that integrate MICP technology with alkali-activated technology.

[0007] To address the shortcomings of existing technologies, this invention proposes a ternary synergistic enhancement strategy of "alkali-activated gelation-microbial mineralization-electric field-directed migration." By gradient domestication of alkali-tolerant microorganisms, they can maintain high urease activity in high-alkalinity slurries. The endogenous calcium source from industrial waste (especially steel slag) provides raw materials for the MIP reaction, reducing the need for external chemical reagents. Simultaneously, an external electric field is introduced to accelerate the directional transport of calcium ions to the microbial enrichment zone through electromigration, neutralizing the local high pH environment, thereby significantly improving the mineralization rate and uniformity. This invention aims to provide a composite grouting material that combines high strength, rapid curing, green and low-carbon characteristics with excellent construction performance, which is of great significance for promoting the resource utilization of industrial solid waste and the development of green reinforcement technologies for geotechnical engineering. Summary of the Invention

[0008] To overcome the shortcomings of existing alkali-activated grouting materials, such as insufficient toughness and susceptibility to shrinkage and cracking, as well as the ineffectiveness of traditional MIP technology in strongly alkaline environments and uneven mineralization, this invention provides a solidification material based on the synergistic effect of MIP and alkali activation, and its preparation method. Through component optimization, gradient acclimatization of alkali-resistant bacteria, and directional control by an applied electric field, the high-value utilization of industrial solid waste and the synergistic improvement of the mechanical properties, impermeability, and durability of soft soil are achieved.

[0009] Technical solution

[0010] A curing material based on the synergistic effect of MICP-alkali activation is composed of a mixture of component A and component B; wherein,

[0011] Component A is an alkali-activated industrial waste slurry, the raw materials of which include: industrial waste, fine sand, water-reducing agent and alkali activator solution;

[0012] Component B is a microbial mineralization solution, which includes: alkali-resistant Bacillus that has been adapted to a gradient alkali, urea, and a calcium source;

[0013] The slurry formed after mixing component A and component B has a pH value of 12-13.

[0014] In a preferred embodiment of the present invention, component A comprises, by mass parts, fly ash, blast furnace slag, and steel slag mixed in a ratio of 1-90:10-80:5-85; preferably, the ratio is 60:20:20. Further, the industrial waste slag requires crushing and grinding to achieve a specific surface area ≥400 m². 2 / kg.

[0015] In a preferred embodiment of the present invention, in component A, the alkaline activator solution is a modified sodium silicate solution, prepared by mixing sodium silicate and sodium hydroxide, with a modulus (i.e., the molar ratio of SiO2 to Na2O) of 1.6 to 2.2; the mass concentration of the alkaline activator solution, i.e., the percentage of the modified sodium silicate solution in the total mass of the entire activator solution, is 35% to 50%.

[0016] The amount of the alkaline activator solution added is 80% to 110% of the mass of the industrial waste residue;

[0017] The amount of fine sand added is 10% to 200% of the mass of the industrial waste residue, preferably 150%.

[0018] The water-reducing agent is a naphthalene-based high-efficiency water-reducing agent (naphthalene sulfonate formaldehyde condensate, FDN-C), and its addition amount is 0.5%~1.0% of the mass of the industrial waste residue.

[0019] In a preferred embodiment of the present invention, the alkali-resistant Bacillus in component B is *Sporosarcina pasteurii*.

[0020] The calcium source is calcium chloride or calcium nitrate;

[0021] The amount of urea added to the microbial mineralizing solution is 15-30 g / L, and the amount of calcium source added is based on Ca... 2+ The concentration is calculated to be 0.2~1.0 mol / L; preferably, the amount of urea added is 20 g / L, and the amount of calcium source added is based on Ca... 2+ The concentration is calculated to be 0.4~0.8 mol / L;

[0022] Before being mixed with component A, the pH of the microbial mineralization solution is adjusted to 8.5-10.0 by adding an alkaline activator solution or a phosphate buffer solution.

[0023] This invention also discloses a method for preparing a cured material based on the synergistic effect of MIP-base activation, comprising the following steps:

[0024] a. Preparation of slurry 1: Weigh fly ash, blast furnace slag, steel slag and fine sand according to the proportion, put them into a cement paste mixer and dry mix them evenly; then add alkali activator solution and water reducing agent, continue to stir to mix thoroughly and evenly, and obtain alkali activated gelling slurry (slurry 1).

[0025] b. Preparation of bacterial solution 2: Add the Bacillus bacterial solution that has been adapted to a gradient alkali, urea and calcium source (such as calcium chloride or calcium nitrate) to water, stir evenly, and obtain bacterial solution 2 containing microorganisms, urea and calcium source;

[0026] c. Mixing: Thoroughly stir and mix the slurry 1 obtained in step a and the bacterial solution 2 obtained in step b to obtain the MIP-alkali-activated synergistic curing material slurry, wherein the pH value of the slurry is in the range of 12~13;

[0027] d. After grouting is completed, a DC electric field is applied to the grout body. Preferably, the DC electric field is applied before the grout body sets.

[0028] In a preferred embodiment of the present invention, in step b, the amount of urea added to the bacterial solution 2 is 20 g / L, and the amount of calcium source added is based on Ca... 2+ The concentration is calculated to be 0.4~0.8 mol / L.

[0029] In a preferred embodiment of the present invention, step b, the gradient alkali adaptation acclimatization, includes the following steps:

[0030] (1) Activation of strains: The Bacillus strains stored at low temperature were inoculated into solid culture medium and activated at 30±1℃ for 24h. Single colonies were picked for later use.

[0031] (2) Primary alkali adaptation culture: The activated Bacillus was inoculated into sterile liquid culture medium and an appropriate amount of alkali activator solution was added to adjust the pH of the system to 10.0±0.2; then it was placed in a constant temperature shaking incubator for primary induction culture. The culture conditions were: temperature 30±1℃, shaking frequency 140±5rpm, culture time 48~72h, to obtain a bacterial suspension with initially improved pH tolerance;

[0032] (3) Advanced alkali adaptation culture: The bacterial suspension was transferred to fresh sterile liquid culture medium with an inoculation volume of 2.0±0.1 mL, and alkali activator solution was added to raise the pH value of the system to 11.0±0.2; the induction culture was continued for 48~72 h under the same temperature control conditions (30±1℃) and shaking parameters (140±5 rpm);

[0033] (4) Gradual increase and obtaining acclimatized bacterial agent: In accordance with the above method, gradually increase the pH value of the culture medium (for example, increase it to 12.0±0.2, 13.0±0.2), repeat the subculture, and finally obtain a highly alkaline tolerant bacterial agent that can grow stably and maintain high urease activity in a highly alkaline environment with a pH of 12~13.

[0034] Preferably, the liquid culture medium used in the above steps has the following formulation: 17 g / L tryptone, 5 g / L ammonium chloride, 3 g / L soybean papain hydrolysate, 2.5 g / L dipotassium hydrogen phosphate, 2.5 g / L glucose, and 20 g / L urea, and the initial pH of the culture medium is 8.6.

[0035] In a preferred embodiment of the present invention, in step c, before the bacterial solution 2 is mixed with the slurry 1, the pH value is adjusted to 8.5~10.0 by adding an alkaline activator solution or a phosphate buffer solution to ensure the activity state of the microorganisms before contact with the high alkaline environment.

[0036] In a preferred embodiment of the present invention, step d involves applying a DC electric field as follows: after grouting is completed, electrodes (anode is a titanium mesh or graphite electrode, cathode is a stainless steel plate) are inserted into the grouting body, and a DC electric field is applied. The electric field parameters are: voltage 1~10V, current density 0.1~2mA / cm². 2 The duration of action is 1 to 24 hours.

[0037] Through the above electric field treatment, on the one hand, the electromigration effect is used to accelerate Ca... 2+ It moves directionally towards the cathode region where microorganisms are enriched, increasing the local calcium ion concentration and promoting the rapid formation of calcium carbonate; on the other hand, it neutralizes local hydroxide ions (OH-) through electrochemical reactions. - This provides a more stable local acid-base environment for microorganisms, thereby maintaining their activity and achieving phased synergistic regulation of "first stimulating gelation, then enhancing mineralization".

[0038] The present invention also discloses the application of the curing material, namely, injecting the curing material into soft soil layers or parts to be reinforced, and applying a DC electric field before the grouting body sets.

[0039] The composite grouting and curing material of this invention achieves its strength and improved durability through a synergistic reinforcing effect among its multiple components. Each component has a clearly defined function and is mutually coupled, jointly constructing a dual-reinforcing structure of "gel framework + mineralization deposition." The specific mechanism is as follows:

[0040] 1. Rapid reaction cementing effect of slag

[0041] Blast furnace slag is rich in glassy aluminosilicates and calcium and magnesium oxides, which undergo rapid dissolution and hydration reactions under the action of an alkaline activator to generate cementitious products mainly composed of hydrated calcium silicate (CSH) and hydrated calcium aluminate (CAH). This process starts within hours after grouting, rapidly forming an initial gel skeleton network that provides early structural support and bonding strength to the grout, effectively solving the problem of insufficient early strength in traditional MICP technology. Simultaneously, the rapid hydration of the slag consumes free water in the system, reducing pore water pressure and accelerating grout thickening and setting.

[0042] 2. Post-activation and filling effect of fly ash

[0043] The spherical glassy particles in fly ash possess potential pozzolanic activity. Under alkaline activation, the active SiO2 and Al2O3 on their surface gradually dissolve and react with Ca(OH)2 released during slag hydration (or directly with alkaline activators), generating additional CSH and zeolite minerals (NASH). This reaction continues for up to 28 days or even longer, providing late-stage strength growth for the material. Simultaneously, the fly ash microspheres, with sizes ranging from 1 to 100 μm, can effectively fill the micropores between slag gel skeletons and soil particles, improving the material's compactness and impermeability. Furthermore, the smooth, spherical surface of fly ash provides an ideal attachment carrier for alkali-resistant Bacillus pasteurellis, promoting biofilm formation and cell immobilization.

[0044] 3. The continuous calcium source and skeletal support function of steel slag

[0045] Steel slag is rich in free CaO, tricalcium silicate (C3S), and dicalcium silicate (C2S), among other alkaline calcium phases. In an alkaline-activated environment, these calcium phases can slowly and continuously release CaO. 2+This provides a calcium source for two processes: firstly, it sustains the alkaline-activated gelation reaction, promoting further formation of CSH gel in the later stages; secondly, it provides the necessary calcium ions for microbially induced calcium carbonate precipitation (MICP), eliminating the need for external chemical reagents such as calcium chloride. The calcium-magnesium-iron solid solution particles in steel slag are hard and can act as a microskeleton in the solidified body, improving the material's resistance to compression and shear. Simultaneously, the trace amounts of Fe and Mg released from steel slag are cofactors for urease-producing microorganisms, effectively promoting enzyme activity and enhancing MIP mineralization efficiency.

[0046] 4. The mineralization "trigger" role of alkali-resistant Bacillus pasteurellii

[0047] This invention utilizes *Bacillus pasteurellii* strains acclimatized to a gradient alkaline environment, capable of tolerating a strongly alkaline environment of pH 12-13. The urease produced by this strain's metabolism can efficiently hydrolyze urea to generate CO3. 2- and NH4 + CO3 2- Then react with Ca in the system 2+ (Mainly released from steel slag and mineral slag) The reaction produces calcium carbonate crystals. These calcium carbonate crystals preferentially nucleate and grow on the surface of existing CSH gels and fly ash microspheres, forming a "gel-crystal" interlocking structure. Microorganisms play a "trigger" role in this process; their mineralization does not occur independently but is precisely deposited at the active sites of the gel framework, avoiding the defects of uneven mineralization distribution and local blockage in traditional MIPs.

[0048] In summary, the solidification material and its preparation method based on the synergistic effect of MIP-alkali activation provided by this invention organically combine microbial induced calcium carbonate precipitation (MICP) technology with an alkali-activated industrial waste cementing system. This fully leverages the synergistic enhancement effect between the alkali-activated cementing reaction and the microbial mineralization reaction, achieving a comprehensive improvement in the strength, impermeability, durability, and environmental friendliness of soft soil reinforcement materials. This invention utilizes industrial solid wastes such as fly ash, blast furnace slag, and steel slag as main raw materials, effectively reducing the use of traditional cement materials, energy consumption, and carbon emissions. Simultaneously, it achieves the resource utilization of industrial solid waste, demonstrating significant green and low-carbon benefits.

[0049] This invention proposes a synergistic enhancement mechanism involving alkali-activated gelation, microbial mineralization, and multi-scale pore filling and particle cementation. Aluminosilicate materials such as fly ash, blast furnace slag, and steel slag in industrial waste undergo dissolution and polymerization reactions under the action of an alkaline activator, forming gelation products mainly composed of hydrated calcium silicate (CSH) gel and hydrated aluminosilicate (NASH) gel, thereby constructing the initial cementation framework and improving the overall strength and stability of the slurry. Simultaneously, urease-active microorganisms in the MICP system produce CO3 through the hydrolysis of urea.2- and with Ca in the system 2+ The reaction produces calcium carbonate crystals. These CaCO3 crystals can deposit on the surface of soil particles, at particle contact points, and within pores, filling soil pores and achieving bio-cementation between particles, thereby further improving the compactness, compressive strength, and impermeability of soft soil. Ultimately, alkali-activated cementation and MIP biomineralization together construct a composite reinforcement structure of "gel cementation-crystal filling-particle bridging," achieving a synergistic improvement in the mechanical and durability properties of soft soil.

[0050] Beneficial effects

[0051] This invention utilizes industrial solid wastes such as fly ash, blast furnace slag, and steel slag as the main cementing raw materials. Through an alkali-activated reaction, a gel structure with cementing properties is formed, achieving high-value resource utilization of industrial waste and reducing the amount of traditional cement materials used. This effectively reduces energy consumption and carbon dioxide emissions, resulting in significant green, low-carbon, and environmentally friendly benefits. Simultaneously, microbial-induced calcium carbonate precipitation (MICP) technology is introduced. Through microbial mineralization, calcium carbonate crystals are generated on the surface of soil particles and inside pores, further filling soil pores and enhancing interparticle cementation, thereby significantly improving the compactness, compressive strength, and impermeability of soft soil. Furthermore, the alkali-activated gelation system and the MIP mineralization system in this invention exhibit a synergistic enhancement effect. Experimental verification (see Comparative Examples 1 and 2) shows that the alkali-activated system (without MIP) has a 28-day strength of 22 MPa, while the MIP system (without alkali activation) has a 28-day strength of 6.5 MPa, with a theoretical sum of 28.5 MPa. In Example 1, the 28-day strength after the synergistic effect of both systems reaches 32 MPa, significantly higher than the sum of their individual strengths, representing a relative increase of 12.3%. This data strongly demonstrates that this invention is not a simple superposition of the effects of each component, but rather produces an unexpected synergistic enhancement effect of "1+1>2". Specifically, the interaction between the alkali-activated gel system and the MIP calcium carbonate deposition is not a simple physical mixing or independent action, but rather exhibits a significant chemical and physical synergistic effect—the gel network provides preferential nucleation sites for calcium carbonate, while the calcium carbonate crystals fill the micropores of the gel framework and bridge the particle interfaces, forming a dense composite structure with interlocking "gel-crystal" structures. This structure cannot be achieved through the superposition of a single system. The gel network formed by alkali activation provides a deposition carrier for calcium carbonate crystals, while the generated CaCO3 crystals can serve as nucleation sites for the gel products, further promoting the densification of the slurry structure, effectively reducing the risk of shrinkage cracking and improving long-term durability. This invention solves the problem of CaCO3 crystal deposition in traditional MIP processes by introducing an external electric field. 2+ With CO3 2-The migration rate is limited by the core technical challenges of free diffusion and uneven mineralization distribution. The electromigration effect under an electric field can directionally accelerate the transport of calcium ions to microbial enrichment areas. Simultaneously, by neutralizing the locally high-alkalinity environment through electrochemical reactions, the calcium carbonate production is increased by 37.8%–72% (see Examples 3-5), and the porosity is reduced by 22%–39%. This achieves spatiotemporal controllability and uniformity of the mineralization reaction, significantly improving the early strength and density of the material. This cured material possesses good flowability, injectability, and rapid curing performance, and can be widely used in tunnel engineering, underground engineering, and soft soil foundation reinforcement for roads, demonstrating high engineering application value and promising prospects for widespread application. Attached Figure Description

[0052] Figure 1 Flowchart of the preparation process of the grouting curing material described in this invention;

[0053] Figure 2 Comparison curve of 3-day compressive strength between the grouting curing material prepared in Example 1 and traditional cement-based grout;

[0054] Figure 3 Comparison curve of 28-day compressive strength between the grouting curing material prepared in Example 1 and traditional cement-based grout;

[0055] Figure 4 The curves (a) and (b) showing the changes in urease activity (expressed as the rate of change in conductivity) of Bacillus pasteurellium under different pH conditions during gradient alkali adaptation acclimatization of the present invention are shown.

[0056] Figure 5 Comparison of scanning electron microscopy (SEM) images of the microstructure of the cured body after adding different components; where (a) is the microstructure of the hardened sample of the alkali-activated cementitious material group, (b) is the microstructure of the hardened sample of the bacterial group, and (c) is the microstructure of the sample with the MICP bacterial solution and alkali-activated material of the present invention added at the same time (Example 1). Detailed Implementation

[0057] The present invention will be described in detail below with reference to embodiments to enable those skilled in the art to better understand the present invention, but the present invention is not limited to the following embodiments. Unless otherwise specified, the raw materials and equipment involved in the embodiments are all conventional commercially available products in the art. Unless otherwise specified, the "industrial waste residue" mentioned in the present invention refers to a mixture of fly ash, blast furnace slag and steel slag; the "liquid-solid ratio" refers to the ratio of the mass of the alkali activator solution to the total mass of the industrial waste residue; the "activator concentration" refers to the percentage of the mass of the modified sodium silicate solution to the total mass of the entire activator solution (i.e., the mixture of modified sodium silicate solution and water).

[0058] (I) Experiment on strain domestication and performance verification

[0059] To verify the effect of gradient alkaline adaptation acclimatization method on improving the ability of Bacillus pasteurellii to maintain urease activity under high alkaline conditions, the conductivity method was used to determine the urease activity of bacteria under different pH conditions.

[0060] Experimental Design: First, a supernatant simulating the alkali-activated system was prepared, with a chemical composition consistent with the liquid phase environment of slurry 1 in Example 1. The pH was adjusted to 9.0, 10.0, 11.0, 12.0, and 13.0 by adding different masses of alkali activator. The bacterial culture (OD) after gradient acclimation was then collected. 600 ≈1.8) Inoculate the above test solutions at a 5% (v / v) inoculum amount into the solutions with different pH values ​​and incubate at 30℃ for 24 h and 48 h, respectively. After incubation, take samples, add 1.0 mol / L urea solution, and record the rate of change of solution conductivity within 3 minutes of reaction using a conductivity meter to characterize urease activity.

[0061] Experimental results are as follows Figure 4 As shown in the figure. The results indicate that after gradient alkali adaptation induction, the strain exhibited the highest urease activity at pH 9.0; the activity decreased slightly as the pH increased to 10.0; a significant trough occurred at pH 11.0; however, when the pH continued to rise to 12.0 and 13.0, the urease activity gradually recovered, with the activity at pH 13.0 approaching its high level at pH 9.0. This experimental data strongly demonstrates that the gradient acclimatization method of this invention effectively enhances the adaptability of Bacillus pasteurella to a strongly alkaline environment, enabling it to continuously decompose urea and induce calcium carbonate precipitation in an alkali-activated grouting material system, providing core microbiological support for the synergistic enhancement effect.

[0062] (II) Formulation optimization and screening experiment

[0063] Before determining the final mix proportions, the effects of alkali activator concentration (i.e., the ratio of the mass of modified sodium silicate solution to the total mass of the activator solution, taken as 0.35, 0.40, 0.45, and 0.50 respectively) and liquid-solid ratio (i.e., the ratio of the mass of the alkali activator solution to the total mass of industrial waste residue, taken as 0.8, 0.9, 1.0, and 1.1 respectively) on the compressive strength of the solidified body were systematically investigated. The industrial waste residue mix proportion was fixed at fly ash: blast furnace slag: steel slag = 60:20:20. The specimens were cured under standard curing conditions (temperature 20±2℃, humidity ≥95%) to the specified age and then subjected to compressive strength tests. The results are shown in Table A-1 (3-day strength, MPa) and Table A-2 (28-day strength, MPa).

[0064] Table A-1 3-day compressive strength (MPa) under different activator concentrations and liquid-solid ratios

[0065]

[0066] Table A-2 28-day compressive strength (MPa) under different activator concentrations and liquid-solid ratios

[0067]

[0068] As shown in Tables A-1 and A-2, under the same liquid-to-solid ratio, the 3-day and 28-day strengths significantly increased with the activator concentration increasing from 0.35 to 0.50. However, at the same activator concentration, reducing the liquid-to-solid ratio (i.e., reducing water consumption) was beneficial for improving strength. Range analysis revealed that the activator concentration had a more significant impact on the 28-day compressive strength (range R = 16.5), greater than the impact of the liquid-to-solid ratio (range R = 9.5). Considering strength, flowability, and economy, the preferred activator concentration is 0.40–0.45, and the preferred liquid-to-solid ratio is 0.8–0.9. The following embodiments will be adapted within this preferred range according to different operating conditions.

[0069] Example 1

[0070] A subway tunnel project in a certain city has a section length of 2.3km, traversing water-rich sand layers and clay interbedded strata. The original design used cement-bentonite two-component grout, but during construction it was found that the initial setting time of the grout was too long (>4h), resulting in excessive ground settlement (maximum settlement of 25mm), and a large amount of cement was used.

[0071] This embodiment utilizes the materials and processes described in this invention. The industrial waste (fly ash, blast furnace slag, steel slag) originates from a nearby steel plant and is ground to a specific surface area of ​​420 m². 2 / kg. Accurately weigh fly ash: blast furnace slag: steel slag according to the mass ratio of 60:20:20, and add fine sand equal to 150% of the total mass of industrial waste. The alkali activator is a modified sodium silicate solution with a modulus of 1.6, the activator concentration (mass ratio) is 0.45, and the liquid-solid ratio is controlled at 0.9. The water-reducing agent (FDN-C) dosage is 0.5%. *Bacillus pasteurellii* was gradually acclimatized to tolerate pH 13, and then cultured on-site in a fermenter to expand to OD. 600 =1.8. The urea concentration in bacterial solution 2 is 20 g / L, and the calcium chloride concentration is 0.6 mol / L. Mix slurry 1 and bacterial solution 2 in proportion and stir for 5 minutes in an on-site mixer.

[0072] The initial setting time of the grouting material prepared in this embodiment was measured to be 45 minutes, the slump to be 260 mm, and the fluidity was good. The grouting pressure was controlled at 0.3~0.4 MPa, and synchronous grouting was carried out through the grouting holes of the tunnel boring machine segments. Supplementary grouting was also carried out in areas with excessive settlement. The application effect is shown in Table 1.

[0073] Table 1. Application Effects and Comparison of Example 1

[0074]

[0075] Note: The traditional cement-based slurry is ordinary Portland cement paste with a water-cement ratio of 0.9. The water-cement ratio is consistent with the liquid-solid ratio in Example 1, and the curing conditions (temperature 20±2℃, humidity ≥95%) are the same as in this example.

[0076] Application test results and Figure 5 The microscopic features are consistent with those of the SEM scan images of the bacterial culture and alkali-activated material.

[0077] Example 2

[0078] A certain cross-sea highway tunnel has a 5.8km long underwater section, with the strata consisting of highly permeable fractured rock (permeability coefficient > 10⁻). 4 The system faces challenges from seawater erosion and high water pressure (cm / s). The original solution used ultrafine cement-water glass slurry, but it experienced frequent leaks during operation and had poor resistance to seawater erosion.

[0079] For the specific conditions described in this embodiment, adaptive adjustments were made to the proportions in Example 1: the industrial waste slag ratio was adjusted to fly ash: blast furnace slag: steel slag = 40:30:30 to increase the proportion of steel slag and provide a more sufficient calcium source; simultaneously, the calcium source was changed to a 0.5 mol / L calcium nitrate solution to avoid introducing chloride ions. To improve the fluidity of high-pressure grouting, the liquid-to-solid ratio was increased to 1.0, and 0.8% naphthalene-based water-reducing agent was added, while the activator concentration was adjusted to 0.40.

[0080] A backward-retreating segmented grouting process was adopted, with a grouting pressure of 0.8~1.0MPa and a grouting diffusion radius of 1.2~1.5m. After grouting, changes in pore water pressure were monitored, and the grouting volume was dynamically adjusted. The initial setting time in this embodiment was measured to be 60 minutes, and the Cl-resistance was [not specified]. - The erosion coefficient is ≥0.95 (28-day immersion). The application effect is shown in Table 2.

[0081] Table 2. Application Effects and Comparison of Example 2

[0082]

[0083] Compared with the 28-day strength (19.0 MPa) corresponding to an activator concentration of 0.40 and a liquid-to-solid ratio of 1.0 in Table A-2, although the measured strength of Example 2 is not listed in the table, it can reach more than 22 MPa according to the verification test of similar formulations. Combined with the contribution of MIP mineralization, the final impermeability grade reaches P12, and the chloride ion diffusion coefficient is reduced by 81%, which fully proves the applicability of this formulation in the seawater erosion environment.

[0084] Example 3

[0085] The grout was prepared and injected according to the proportions and process of Example 1. After injection (before the final setting of the grout body), electrodes (anode: titanium mesh, cathode: stainless steel plate) were inserted into the grout body, and a 5V DC electric field was applied with the current density controlled at 1mA / cm². 2 The electric field was applied continuously for 6 hours. During the application of the electric field, the slurry temperature was monitored and controlled in real time to ensure it did not exceed 35°C. After the electric field was applied, the slurry was allowed to cure at 25°C until the test age.

[0086] This embodiment aims to verify the promoting effect of electric field on MICP mineralization efficiency. The performance test results are shown in Table 3.

[0087] Table 3. Performance Comparison of Example 3 (with electric field) and Example 1 (without electric field)

[0088]

[0089] Example 4

[0090] To explore low-energy-consumption and low-equipment-loss electric field application modes, this embodiment adopts a low-voltage, long-term processing strategy. The grouting material ratio and construction process are the same as in Embodiment 1. After grouting, a DC electric field is applied, with the voltage set to 1V and the current density to 0.1mA / cm². 2 The continuous action time was 24 hours. The maintenance and testing conditions were the same as in Example 3, and the performance test results are shown in Table 4.

[0091] Table 4 Performance Comparison between Example 4 (Low Voltage Long Duration) and Example 1 (No Electric Field)

[0092]

[0093] Results analysis: Under a low voltage of 1V and a long-term (24h) electric field, Ca 2+ and CO3 2- Driven by a weak but continuous electric field, the electrode slowly migrates to the microbial enrichment area. The calcium carbonate production is 37.8% higher than that of the group without an electric field, the 3-day compressive strength is 18.8% higher, the porosity is reduced by 22.2%, and there is no obvious corrosion on the electrode surface. This indicates that the low voltage condition has less impact on equipment loss and is suitable for engineering scenarios with high requirements for energy consumption and electrode life.

[0094] Example 5

[0095] To meet the requirements of rapid construction, this embodiment employs a high-voltage, short-time electric field treatment strategy. The grouting material ratio and construction process are the same as in Embodiment 1. After grouting, a DC electric field is applied, with the voltage set at 10V and the current density at 2.0mA / cm². 2 The electric field was applied for 1 hour. The slurry temperature was strictly monitored during the electric field application, and a circulating cooling water system was used to ensure the temperature remained ≤35℃. The performance test results are shown in Table 5.

[0096] Table 5. Performance Comparison between Example 5 (High Voltage Short Time) and Example 1 (No Electric Field)

[0097]

[0098] Results Analysis: Under a 10V high voltage and a short-duration (1h) electric field, the ion migration rate was significantly accelerated, the calcium carbonate formation was increased by 72.0% compared to the group without an electric field, the 3-day compressive strength increased by 43.8%, and the porosity decreased by 38.9%. Slight oxidation appeared on the electrode surface, which is within an acceptable range and does not affect single-project applications. The results indicate that short-duration high voltage can significantly accelerate ion migration, with the most significant improvement in mineralization efficiency. Although slight oxidation occurred on the electrode surface, it was within a controllable range, making it suitable for emergency repair projects with extremely high early strength requirements.

[0099] Example 6

[0100] A soft soil foundation reinforcement project for a road in a coastal area. The original soft soil has a natural water content of approximately 38% and a liquid limit of 52%. The bearing capacity of the foundation does not meet the design requirements. The material of this invention is used to perform in-situ solidification treatment on the soft soil.

[0101] Based on the characteristics of soft soil, the solidification material formula was adjusted to: fly ash: blast furnace slag: steel slag powder = 7:9:4 in industrial waste residue; 9.6% NaOH solution (8 mol / L) and 14.4% water glass solution were added, accounting for 9.6% of the total waste residue mass. In the MICP system, the addition ratio of Bacillus pasteurellium inoculum, urea, and calcium chloride was controlled at 3:1:1, with an inoculum concentration of approximately 1.5 × 10⁻⁶. 8 CFU / mL, final urea concentration 20 g / L. The overall liquid-to-solid ratio (the ratio of the mass of the alkali activator solution to the industrial waste residue, with the moisture content of the soft soil calculated separately) was controlled at 0.45. After the solidification material and soft soil were thoroughly mixed in a forced mixer, they were compacted in layers, covered with a thin film to retain moisture, and cured at 25℃ for 28 days. The performance test results are shown in Table 6.

[0102] Table 6. Application Effects of Example 6 (Curing)

[0103]

[0104] Note: The traditional alkali-activated solidified soil mentioned above is a control sample that uses the same industrial waste residue ratio (fly ash: slag: steel slag = 7:9:4), and is alkali activated with the same amount of NaOH solution (8mol / L, 9.6%) and water glass solution (14.4%), but without the addition of MIP bacterial solution, urea and calcium source.

[0105] Example 7

[0106] A river dredging project in a certain city generated a large amount of high-moisture-content organic sludge, and traditional stockpiling disposal poses a risk of secondary pollution. This invention utilizes a material to solidify the dredged sludge in situ, and the solidified product is then used for backfilling municipal roads.

[0107] To address the high organic matter and fine particle content of the sludge, the optimized material ratio was: 40% fly ash, 35% blast furnace slag, 15% steel slag, and 10% red mud (based on total industrial waste). The alkali activator was a mixture of 8 mol / L NaOH solution and water glass solution with a modulus of 1.4. In the MICP system, the bacterial concentration was cultured to 1.8 × 10⁻⁶. 8 The concentrations of CFU / mL, urea, and calcium nitrate were both 0.6 mol / L. The curing process was the same as in Example 6, and the application results are shown in Table 7.

[0108] Table 7. Application Effects of Example 7 (Sludge Solidification)

[0109]

[0110] Note: The traditional cement-stabilized soil mentioned is ordinary silicate cement-stabilized soil with a dosage of 15% (as a percentage of the mass of wet silt), a water-cement ratio of 0.45, and curing conditions consistent with those in this embodiment.

[0111] Comparative Example 1

[0112] To highlight the guiding and enhancing effect of the alkali-activated gel skeleton on MICP mineralization in this invention, Comparative Example 1 was set up. Except for the absence of fly ash, blast furnace slag, steel slag, and alkali activator, all other materials and processes were consistent with Example 1. That is, only fine sand was used as aggregate, and acclimatized Bacillus pasteurellium culture (OD200) was added. 600 =1.8), urea (20g / L) and calcium chloride (0.6mol / L), mixed and then injected.

[0113] Test results: 3-day compressive strength was only 2.5 MPa (16% of Example 1); 28-day compressive strength was only 6.5 MPa (23% of Example 1); impermeability coefficient was 1×10⁻⁶. -5 cm / s (three orders of magnitude higher than in Example 1); calcium carbonate formation was 5.8%; the intensity dispersion coefficient (CV) was as high as 32% (12% in Example 1), indicating extremely uneven mineralization distribution. Microstructure ( Figure 5 a) The calcium carbonate is shown to be scattered and without a continuous cemented skeleton.

[0114] Compared with Example 1, the present invention guides the uniform deposition of calcium carbonate through alkali-activated gel network, resulting in a 5.4-fold increase in strength at 3 days, a 3.3-fold increase in strength at 28 days, a 3-order-of-magnitude improvement in impermeability, and a 167% improvement in strength uniformity, thus solving the fundamental defects of traditional MCP in terms of "low strength and uneven distribution".

[0115] Comparative Example 2

[0116] To highlight the reinforcing effect of MIP mineralization on the performance of alkali-activated materials in this invention, Comparative Example 2 was set up. Except for the absence of microbial inoculum, urea, and calcium chloride, the other material ratios and processes were kept consistent with Example 1, that is, only alkali-activated industrial waste slurry was used for grouting.

[0117] Test results: 3-day compressive strength was 9 MPa; 28-day compressive strength was 22 MPa (21% lower than Example 1); impermeability coefficient was 8 × 10⁻⁶. -8 cm / s (one order of magnitude higher than Example 1); porosity 22%. Microstructure ( Figure 5 (b) A clear gel structure is visible, but the micron-sized pores are not filled. Compared to Example 1, the calcium carbonate crystals generated by MICP in this invention effectively fill the micropores of the gel framework. Figure 5 c) Forming a "gel-crystal" interlocking dense structure, which increases the 28-day strength by 27% and the impermeability by one order of magnitude, significantly improving the early strength and density of the material.

[0118] Application test results and Figure 5 The microscopic features of the SEM scan images of the material with added alkali are consistent.

[0119] Comparative Example 3

[0120] The 28-day compressive strengths of Comparative Example 1 (MICP only) and Comparative Example 2 (alkali activation only) were arithmetically summed to obtain the theoretical superimposed strength: 6.5 MPa + 22 MPa = 28.5 MPa. The measured 28-day compressive strength of Example 1 of this invention (alkali activation + MICP synergy) was 32 MPa.

[0121] Calculate the synergistic contribution: Synergistic enhancement value = 32 MPa - 28.5 MPa = 3.5 MPa; Relative increase = 3.5 / 28.5 × 100% = 12.3%.

[0122] This result clearly demonstrates that the interaction between the alkali-activated gel framework and MICP calcium carbonate deposition is not a simple physical mixing or independent process, but rather a significant synergistic effect of chemical and physical processes. The gel network provides preferential nucleation sites for calcium carbonate, while the calcium carbonate crystals fill the micropores of the gel framework and bridge the particle interfaces, forming a dense composite structure with interlocking gel-crystal structures (see...). Figure 5 (c) This structure cannot be achieved by superimposing a single system. This comparative example powerfully demonstrates the objective existence and significant technical advantages of the synergistic effect described in this invention.

[0123] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A curing material based on the synergistic effect of MIP-alkali activation, comprising a mixture of component A and component B; characterized in that: Component A is an alkali-activated industrial waste slurry, the raw materials of which include industrial waste, fine sand, water-reducing agent and alkali activator solution; Component B is a microbial mineralization liquid, which contains alkali-resistant Bacillus that has been adapted to gradient alkali, urea and calcium source; the slurry formed after mixing Component A and Component B has a pH value of 12-13.

2. The curing material based on the synergistic effect of MIP-alkali activation according to claim 1, characterized in that: In component A, the industrial waste residue, by mass parts, is a mixture of fly ash, blast furnace slag, and steel slag in a ratio of 1–90:10–80:5–85; the industrial waste residue needs to be crushed and ground to ensure a specific surface area ≥400 m². 2 / kg.

3. The curing material based on the synergistic effect of MIP-alkali activation according to claim 1, characterized in that: In component A, the alkaline activator solution is a modified sodium silicate solution, prepared by mixing sodium silicate and sodium hydroxide, with a modulus (i.e., the molar ratio of SiO2 to Na2O) of 1.6 to 2.2; the mass concentration of the alkaline activator solution, i.e., the percentage of the modified sodium silicate solution in the total mass of the entire activator solution, is 35% to 50%. The amount of the alkaline activator solution added is 80% to 110% of the mass of the industrial waste residue; The amount of fine sand added is 10-200% of the mass of the industrial waste residue; The water-reducing agent is a naphthalene-based high-efficiency water-reducing agent, and its addition amount is 0.5% to 1.0% of the mass of the industrial waste residue.

4. The curing material based on the synergistic effect of MIP-alkali activation according to claim 1, characterized in that: In component B, the alkali-resistant Bacillus is *Sporosarcina pasteurii*. The calcium source is calcium chloride or calcium nitrate; The amount of urea added to the microbial mineralizing solution is 15-30 g / L, and the amount of calcium source added is based on Ca... 2+ The concentration is calculated to be 0.2–1.0 mol / L; preferably, the amount of urea added is 20 g / L, and the amount of calcium source added is based on Ca... 2+ The concentration is calculated to be 0.4–0.8 mol / L; Before being mixed with component A, the pH of the microbial mineralization solution is adjusted to 8.5–10.0 by adding an alkaline activator solution or a phosphate buffer solution.

5. A method for preparing a cured material based on the synergistic effect of MIP-base activation as described in any one of claims 1-4, characterized in that, Includes the following steps: a. Preparation of slurry 1: Weigh fly ash, blast furnace slag, steel slag and fine sand according to the proportion, mix them, add alkali activator solution and water reducing agent, stir evenly to obtain alkali activated gelling slurry, i.e. slurry 1; b. Preparation of bacterial solution 2: Add the Bacillus bacterial solution that has been adapted to gradient alkali, urea and calcium source to water, stir evenly, and obtain bacterial solution 2 containing microorganisms, urea and calcium source; c. Mixing: Thoroughly stir and mix the slurry 1 obtained in step a and the bacterial solution 2 obtained in step b to obtain the MIP-alkali activation synergistic curing material slurry, wherein the pH value of the slurry is in the range of 12 to 13; d. After grouting is completed, apply a DC electric field to the grouting body.

6. The method for preparing the cured material based on the synergistic effect of MICP-alkali activation according to claim 5, characterized in that: In step b, the amount of urea added to the bacterial solution 2 is 20 g / L, and the amount of calcium source added is based on Ca... 2+ The concentration is estimated to be 0.4–0.8 mol / L.

7. The method for preparing the cured material based on the synergistic effect of MICP-base activation according to claim 5, characterized in that, In step b, the gradient alkali adaptation acclimatization includes the following steps: (1) Activation of strains: The Bacillus strains stored at low temperature were inoculated into solid culture medium and activated at 30±1℃ for 24h. Single colonies were picked for later use. (2) Primary alkali adaptation culture: The activated Bacillus was inoculated into sterile liquid culture medium and an appropriate amount of alkali activator solution was added to adjust the pH of the system to 10.0±0.2; then it was placed in a constant temperature shaking incubator for primary induction culture. The culture conditions were: temperature 30±1℃, shaking frequency 140±5rpm, culture time 48~72h, to obtain a bacterial suspension with preliminary improved pH tolerance; (3) Advanced alkaline adaptation culture: The bacterial suspension was transferred to fresh sterile liquid culture medium with an inoculation volume of 2.0±0.1 mL, and alkaline activator solution was added to raise the pH value of the system to 11.0±0.2; the induction culture was continued for 48~72 h under the same temperature control conditions and shaking parameters. (4) Gradual increase and obtaining acclimatized bacterial agent: Following the above method, gradually increase the pH value of the culture medium, repeat the subculture, and finally obtain a highly alkaline tolerant bacterial agent that can grow stably and maintain high urease activity in a highly alkaline environment with a pH of 12-13.

8. The method for preparing the cured material based on the synergistic effect of MIP-base activation according to claim 5, characterized in that: In step c, before the bacterial solution 2 is mixed with the slurry 1, its pH value is adjusted to 8.5-10.0 by adding an alkaline activator solution or a phosphate buffer solution to ensure the activity state of the microorganisms before they come into contact with a high-alkaline environment.

9. The method for preparing the cured material based on the synergistic effect of MICP-base activation according to claim 5, characterized in that, In step d, the method for applying the DC electric field is as follows: after grouting is completed, electrodes are inserted into the grouting body, with the anode being a titanium mesh or graphite electrode and the cathode being a stainless steel plate. A DC electric field is then applied, wherein the electric field parameters are: voltage 1–10V, current density 0.1–2mA / cm². 2 The duration of action is 1 to 24 hours.

10. A curing method for a curing material based on the synergistic effect of MIP-alkali activation, characterized in that: The curing material according to any one of claims 1-4 or the curing material prepared by any one of claims 5-9 is injected into the soft soil layer or the part to be reinforced, and a DC electric field is applied before the grouting body is fully set.